Pengembangan Sistem Berbasis Pengetahuan untuk Pengendalian Kualitas pada Proses Frontune Produk Infrared (Studi Kasus pada PT Perkin Elmer Optoelektronics Batam) - Wisaksono, Mohammad; Hisjam, Muh.; Pujiyanto, Eko (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2003)
SBPPK (sistem berbasis pengetahuan untuk pengendalian kualitas) is a knowledge based system which using human knowlwdge that being planted in computer to help solving problem that needs special skill or expertise. This system can be used by anyone whose not an expert to increase their skill in specivic domain problem solving.SBPPK is designed by integrating quality control function that consist of X-R chart, NP chart, process capability, pareto diagram and also the ability to analyze the output. By using this system manufacturing statistical quality control application will take shorter time.